Tahfiz Al-Qur'an Education System in Robitotul Istiqomah Huristak Islamic Boarding School, Padang Lawas Regency - Sinta Lesmarani Siregar; Nurmawati Nurmawati; Yusnaili Budianti (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
The success of an institution at the pesantren level cannot be separated from the range of systems applied, both the strategy and the curriculum used. Likewise, the implementation of memorizing the Qur'an requires a method and technique that can facilitate these efforts, so that it can work well. The purpose of this study is to analyze the tahfiz Al-Qur'an education system, find out how the strategies used in tahfiz Al-Qur'an education are, and what are the supporting and inhibiting factors in tahfiz Al-Qur'an education at the Robitotul Istiqomah Islamic Boarding School. The method used in this research is to use a qualitative descriptive approach. The results of this study indicate that the planning of Tahfiz Al-Qur'an at the Robitotul Istiqomah Islamic Boarding School does not use a syllabus or RPP (Learning Program Design) but uses and makes a plan using the Tahfiz Al-Qur'an book. By making the Tahfiz Al-Qur'an book, it was developed from the coordination of Tahfiz Al-Qur'an and Teacher Tahfiz. The methods used in learning are the tahfiz method, the Wahdah method, the Sima'i method, the combined method, and the Jama'i method. And Evaluation of tahfiz Al-Qur'an coaching for students is carried out once a month using an assessment in the form of a rote deposit system.